Toxicological evaluation of mature-green and breaker tomato extracts using fertile duck embryos - Ancheta, Flordivina Chiong (1999)
The tomato fruit, Lycopersicon esculentum, is one of the major crops produced and consumed in the country. However, the mature-green tomatoes that are usually eaten raw contain the toxic glycoalkaloid α-tomatine which exhibits in vitro toxicity to a wide variety of microorganisms and animals. This makes the consumption of large amounts of the commodity, and consequently, the alkaloid, a possible risk to human health. Evaluation of the relative toxicity of mature-green and breaker tomato extracts using duck eggs - the laboratory specimen- was performed in three trials. For each trial, two sets of five day-old duck embryos were inoculated separately with 0.1 ml mature-green and breaker tomato extracts. After a four-day incubation period at 38.9°C and 63% RH along with the open and closed, uninoculated controls, the number of viable duck eggs was obtained and analyzed. The mean percentage viability of specimens inoculated with the mature-green and beaker tomato extracts were 53.33% and 73.33%, respectively. Those used as open controls had an average of 93.33% viability while the closed controls yielded 98.33% viability. Analysis of variance (α=0.05) showed that the effects of the extracts on the viability of the embryos were significantly different from those of the control groups. Moreover, the effect of the mature-green tomato extract on the observed viability of the embryos was significantly more severe than the effect of the breaker tomato extract. As such, the mature-green tomato extract is relatively more toxic than the extract of breaker tomatoes.